Efficiency of rainwater harvesting systems in commercial buildings - Sakson-Sysiak, Grażyna; Zyzik, Przemysław (Instal, 2024)
Occurring shortages of water and the increasing price of potable water more and more often encourage investors to look for alternative sources of supply to water supply systems. Rainwater harvesting systems and its use for purposes that do not require drinking water quality are applicable not only in residential buildings, but also in commercial, service, sports and industrial buildings. The article presents the results of functioning analysis of such solutions in two facilities: a car dealership and a petrol station. The size of the systems and the purpose of the rainwater at the two sites are different, as is their location. Based on daily data on the of precipitation depth in 2018-2022, the efficiency and potential capabilities of the systems in both facilities in relation to the specified rainwater demand, as well as the payback time of investment outlays were established. Although the system did not fully cover the demand for non potable water in both facilities, their use can be considered economically viable. This type of analysis, as described in the article, enable the selection of appropriate parameters when designing rainwater harvesting systems and make it easier for investors to decide on the use of such solutions in constructed facilities.